The Dozen Things Experimental Economists Should Do (More of). - Czibor, Eszter; Jimenez‐Gomez, David; List, John A. (Southern Economic Journal, 2019)
What was once broadly viewed as an impossibility—learning from experimental data in economics—has now become commonplace. Governmental bodies, think tanks, and corporations around the world employ teams of experimental researchers to answer their most pressing questions. For their part, in the past two decades academics have begun to more actively partner with organizations to generate data via field experimentation. Although this revolution in evidence‐based approaches has served to deepen the economic science, recently a credibility crisis has caused even the most ardent experimental proponents to pause. This study takes a step back from the burgeoning experimental literature and introduces 12 actions that might help to alleviate this credibility crisis and raise experimental economics to an even higher level. In this way, we view our "12 action wish list" as discussion points to enrich the field.